Problem-Based Learning to Improve Elementary School Students' Understanding of Mathematical Concepts - Faridatul Munawaroh; Ayok Ariyanto; Muh. Tajab (JIE (Journal of Islamic Education), 2025)
Mathematics learning in elementary schools still faces low student conceptual understanding due to the dominance of lecture and teacher-centred learning methods. Students tend to memorise formulas without understanding the application of concepts in everyday life. This study aims to analyse the implementation and effectiveness of the Problem-Based Learning (PBL) model in improving elementary school students' mathematical conceptual understanding and identify supporting factors and obstacles to its implementation. This study adopted a qualitative case study design at SDN 2 Sendang, Ponorogo. Data collection involved participatory observation, structured interviews, and documentation. Primary data sources included the principal, teachers, and fifth-grade students, while secondary data sources included learning modules, evaluation results, documentation, and school archives. The researchers applied the Miles and Huberman model to analyse the data through data reduction, data presentation, and conclusion drawing, while source and technique triangulation ensured data validity. The results showed that the implementation of PBL through six main steps, namely orienting students to the problem, organising students for learning, guiding investigation, developing and presenting the work, evaluating problem-solving, and reflecting and applying, was able to increase active involvement, critical thinking skills, and students' understanding of mathematical concepts. Students become more active in discussions, ask questions, and are able to connect mathematical concepts to real-world situations. The implementation of PBL also has an impact on improving learning outcomes, as seen in the increase in average student report card grades from "inadequate" to "good." This study concludes that PBL is effective in improving elementary school students' understanding of mathematical concepts. However, the study is still limited to one school with a limited number of subjects.